GE_GERICHTE A/1663/2023 vom 31. Januar 2024 - GE Cour de justice (2024)
AMENDE;DÉCHET DE CHANTIER | LGD.17; LGD.43; LPE.7.al6; LPE.31; Règlement LC 44 911 Versoix.24.al8; Règlement LC 44 911 Versoix.39.al1